RESEARCH OF FIRMNESS OF CONVECTIV MOTION WITH PARNIM TYPE OF SPEED - Негрич, Василь Васильович; Дем’янчук, Ярослав Михайлович; Процюк, Галина Ярославівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We investigate the hydrodynamic stability of viscous incompressible fluid located between vertical parallel surfaces . Considered free convection with an even velocity profiles . For research use variational principle of non-equilibrium thermodynamics – the method of local potential. Determine the critical Grashof criterion , depending on the Prandtl number and value of the wave number at which the transition from simple to complex dissipative structures. Also take into account the angle of the layer with respect to the gravitational field. The method of calculation using only one test feature provides comparable results with the kinetic method , using complex test functions.